Transformation in site monitoring practices through risk based monitoring - Khare, Anubhav (International Journal of Clinical Trials, 2016)
As the current trends in clinical trial industry, is evolving day by day and adopting upcoming technology to integrate data from different sources into risked based monitoring (RBM) Portal, to increase efficient tracking system in a way that help in understanding site characteristic and make on-site monitoring visit more focused and accurate. Transformation from traditional monitoring method to RBM solution will significantly improve quality of data and will also reduce study risk and time. RBM is a standardized, systematic approach to identify and assess potential risk.